2018
DOI: 10.5194/acp-18-1437-2018
|View full text |Cite
|
Sign up to set email alerts
|

Representation of solar tides in the stratosphere and lower mesosphere in state-of-the-art reanalyses and in satellite observations

Abstract: Abstract. Atmospheric solar tides in the stratosphere and the lower mesosphere are investigated using temperature data from five state-of-the-art reanalysis data sets (MERRA-2, MERRA, JRA-55, ERA-Interim, and CFSR) as well as TIMED SABER and Aura MLS satellite measurements. The main focus is on the period 2006-2012 during which the satellite observations are available for direct comparison with the reanalyses. Diurnal migrating tides, semidiurnal migrating tides, and nonmigrating tides are diagnosed. Overall t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 54 publications
(93 reference statements)
0
30
0
Order By: Relevance
“…The dynamic fields of temperature and wind fluctuations induced by tides are similarly related to the polarization relation of gravity waves. Such a polarization relation for tides was theoretically derived from the primitive equations for fluctuations of an atmosphere without dissipation by She et al (2016). They showed that there is a fixed relation between both wind components and the temperature fluctuations induced by tides from the investigation of Na lidar measurements and model predictions from the Climatological Tidal Model of the Thermosphere (CTMT) based on the Hough mode extension (HME) technique in the MLT region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic fields of temperature and wind fluctuations induced by tides are similarly related to the polarization relation of gravity waves. Such a polarization relation for tides was theoretically derived from the primitive equations for fluctuations of an atmosphere without dissipation by She et al (2016). They showed that there is a fixed relation between both wind components and the temperature fluctuations induced by tides from the investigation of Na lidar measurements and model predictions from the Climatological Tidal Model of the Thermosphere (CTMT) based on the Hough mode extension (HME) technique in the MLT region.…”
Section: Introductionmentioning
confidence: 99%
“…A derivation and affirmation of a tidal polarization relation would lead to a possibility of deducing an unknown tidal field from another observed tidal field and are therefore also highly recommended for the altitude range below the mesopause region. For a westward-propagating monochromatic wave with a single zonal wave number s, the polarization relation between the temperature tide T and the zonal wind tide u derived by She et al (2016) is…”
Section: Introductionmentioning
confidence: 99%
“…In parallel to the development of new measurement techniques most important general circulation models for numerical weather prediction and reanalysis have extended their lids further into the middle atmosphere due to the broad evidence for the influence of middle-atmospheric dynamics on tropospheric weather and climate (e.g. Baldwin and Dunkerton, 2001;Scaife et al, 2008;Kidston et al, 2015;Garfinkel et al, 2017). The most recent example of this trend towards increased model tops is the European Centre for Medium-Range Weather Forecast (ECMWF) ERA5 reanalysis released in July 2017, which extends up to 0.1 hPa, one pressure decade higher than its predecessor ERA-Interim.…”
Section: Introductionmentioning
confidence: 99%
“…Data are considered at 1 km intervals from 15 to 50 km. It is known that the vertical resolution of RO-derived temperature profiles is 0.5 km in the troposphere and 2 km in the stratosphere (Kursinski et al, 1997;Scherllin-Pirscher et al, 2017). COS-MIC temperatures are smaller by 2 to 3 K than SABER temperatures across all latitudes below 0.3 hPa and larger above this altitude.…”
Section: Data and Samplingmentioning
confidence: 96%